Manufacturing decline and house price volatility - Isaiah Hull; Conny Olovsson; Karl Walentin; Andreas Westermark (Sveriges Riksbank, 2018)
Using a unique dataset of all Swedish housing transactions over the 2009-2017 period, we find that an increase in manufacturing's share of employment is positively associated with house price growth volatility and negatively associated with risk-adjusted housing returns. Both effects appear to be related to manufacturing's impact on firm concentration and employment volatility. Moreover, as we demonstrate in an application, our results have implications for portfolio choice. They also suggest that the manufacturing decline since 1970 could account for a 32% reduction in house price volatility in Sweden, and similar reductions in the U.S., U.K., and Japan.
Keywords: 330; House Prices; Portfolio Choice; Manufacturing; Volatility